Q. 95.0( 3 Votes )


Determine whethe

Answer :


Let p(x) = 9x 2 -3x-2
If x = -1/3 is a zero of the polynomial p(x), then it must satisfy p(-1/3) = 0.

So, on putting x = -1/3 in the above equation, we get:

p(-1/3) = 9(-1/3) 2 - 3(-1/3) - 2

= 1 + 1 - 2

= 2 – 2

= 0.

Therefore the given value of x is a zero of the given polynomial.
If x = 2/3 is a zero of the polynomial p(x), then it must satisfy p(2/3) = 0.

So, on putting x = 2/3 in the above equation, we get:

p(2/3) = 9(2/3) 2 - 3(2/3) - 2

= 4 - 2 - 2

= 4 – 4

= 0.

Therefore the given value of x is not a zero of the given polynomial.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Draw the graph ofNCERT - Mathematics